2014
DOI: 10.1007/s00228-014-1723-9
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study to assess the influence of an enhanced medication plan on patient knowledge at hospital discharge

Abstract: The provision of an EMP improves information transfer and therefore increases the patients' knowledge of their individual drug treatment without prolonging the overall discharge process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 32 publications
0
30
0
2
Order By: Relevance
“…Implementation of an enhanced medication plan as an adjunct to the discharge conversation between physician and patient improved information transfer and patients’ knowledge of their drug treatment in a cohort of patients from several internal clinics in a university hospital. Interestingly, the intervention did not prolong the overall discharge process 21. Although, to date, a clear survival benefit of in-hospital or discharge education could not be demonstrated, prior data have suggested that discharge education may result in fewer days of hospitalization, lower costs, and lower mortality rates within a 6-month follow-up 24…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Implementation of an enhanced medication plan as an adjunct to the discharge conversation between physician and patient improved information transfer and patients’ knowledge of their drug treatment in a cohort of patients from several internal clinics in a university hospital. Interestingly, the intervention did not prolong the overall discharge process 21. Although, to date, a clear survival benefit of in-hospital or discharge education could not be demonstrated, prior data have suggested that discharge education may result in fewer days of hospitalization, lower costs, and lower mortality rates within a 6-month follow-up 24…”
Section: Discussionmentioning
confidence: 95%
“…Patients who receive structured in-hospital education have higher knowledge scores at discharge and 1 year later when compared with those who did not receive in-hospital education 20. Among the strategies to improve recall of medical advice, complementing verbal information with written instructions improved medication recall in a broad spectrum of patient populations 2123. Implementation of an enhanced medication plan as an adjunct to the discharge conversation between physician and patient improved information transfer and patients’ knowledge of their drug treatment in a cohort of patients from several internal clinics in a university hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention measures were adapted to the requirements of doctors in private practice after optimized communication with the hospitals. We did not aim to study the effect of individual modules or to evaluate the benefit of medication checks; other studies have already done so (1,2). Studies that were conducted in non-German speaking countries have shown that multifactorial problems at interfaces can be solved quickly by combining several measures in medication management (3).…”
Section: In Replymentioning
confidence: 99%
“…The authors studied the two interfaces when a patient passes from one care sector into another with regard to their implications for medication, and they attempted to structure this (1). While the title implies a study of an intervention after discharge, what was actually studied were several interventions in an inpatient setting, whose respective proportion in the overall result is not easy to identify.…”
mentioning
confidence: 99%
“…Patients should be educated and encouraged to become more engaged with their healthcare management, including asking any questions to understand the intended use of all medications. A recent study showed how reviewing enhanced medication plans with patients upon hospital discharge improved patient knowledge of their individual medication treatment without prolonging the overall process [17]. Although this study was conducted in the inpatient setting, it highlights how process improvements can improve the quality of care and patient satisfaction without requiring additional time.…”
Section: Improvement In Processes Of Carementioning
confidence: 99%